Hadassah eaudiobook One night with the king. - Tenney, Tommy (Recorded Books Inc., 2015)
Best-selling author and inspirational speaker, Tommy Tenney teams up with Mark Andrew Olsen to deliver a mesmerizing tale of historical fiction. Favorably compared to Anita Diamant's The Red Tent for its unexpected plot twists, Hadassah is the fictional account of the Bible's Esther, the Jewish peasant girl who became queen of Persia.